HUBUNGAN POLA KOMUNIKASI KELUARGA DENGAN TINGKAT DEPRESI LANJUT USIA TAHUN 2018 - TJUT ALINI (LP2MTBM MAKARIOZ, 2019)
The pattern of family communication is the dominant thing in dealing with depression problems. Good family communication in the form of family support can help the elderly in facing life problems and it will be difficult to experience depression. The problem of the elderly can be overcome by giving motivation in the form of good communication. This study aims to identify the relationship of family communication patterns with the level of elderly depression. The design of this study was cross sectional. The population of this study were elderly people aged 60-80 years both women and men who lived with a sample family of 30 respondents. The study was conducted in May-June 2018. The results of the study were analyzed by Chi-Square Test to see the relationship between the two variables, namely family communication patterns and the level of elderly depression, then the results of the study were presented using frequency distribution tables. The results of the study were 24 people (46.6%) respondents who had dysfunctional family communication patterns, and as many as 6 people (10.0%) had functional communication patterns. 1 person (0.33%) normal, 9 people (30.0%) mild to moderate depression, 20 people (66.6%) major depression. The results of the statistical test were obtained p = 0.003 (p <0.05) which showed that there was a significant relationship between family communication patterns and the level of elderly depression. Suggestion to the village head to make an activity that involves the elderly towards the elderly community so that they can share and share stories with their peers.